EFEKTIVITAS PENERIMAAN PAJAK BUMI DAN BANGUNAN PADA DINAS PENDAPATAN DAERAH (DIPENDA) KOTA PEKANBARU - HANDAYANA, SARITA; KHAIRANI, TUTI (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Pekanbaru is one of the autonomy area that paid the outcome both of regular andbuilding outcome. This case need biger fund. Doing activity in this area, DIPENDAas organizer of this income area should able increasing potentials of area’sincoming and another area optimally including of acceptance Land and BuildingTax. But in fact, for years recently acceptance Land and Building Tax is not reachingthe target. Based on that result, the expert do a research about The effectiveness ofacceptance Land and Building Tax in Pekanbaru . the problem is how Theeffectiveness of acceptance Land and Building Tax at DIPENDA, Pekanbaru andwhat factors are obstruct it. The purpose of this research is to know the effectivenessof acceptance Land and Building Tax at DIPENDA in Pekanbaru and what factorsare obstruct it. This research use qualitative descriptive method with technique ofcollecting data is observation and interviewing is getting from informant that havebeen chosen based on Snowball sampling technique. The result of analyze the datafrom qualitative descriptive method find that acceptance Land and Building Tax atDIPENDA, Pekanbaru is not effective yet, because from reanalyze of taxing dutystill is not effective yet, and also giving claim actively from warning and in giving atarget is not suitable. The reason is lack of realization in society, less of humanresource and less of discipline in giving a claim and double owning tax.Keywords: Land and Building Tax, Effectiveness, Resource Approach, ProcessApproach, Goals Approach.